Analysis of linearity and frequency response of a novel piezoelectric flextensional actuator using a homodyne interferometer and the J(1)-J(4) method - Marcal, Luiz Antonio Perezi; Leao, Jose Vital Ferraz; Nader, Gilder; Higuti, Ricardo Tokio [UNESP]; Kitano, Claudio [UNESP]; Silva, Emilio Carlos Nelli (Institute of Electrical and Electronics Engineers (IEEE), 2007)
Piezoelectric transducers are widely used in high-resolution positioning systems. This paper reports the experimental analysis of a novel piezoelectric flextensional actuator (PFA), which is designed by using the topology-optimization method through a low-cost homodyne Michelson interferometer. By applying the J(1) - J(4) method for signal demodulation, which provides a linear and direct measurement of dynamic optical phase shift independent of fading, the nanometric displacements of the PFA were determined. Linearity and frequency response of the PFA were evaluated up to 50 kHz. PFA calibration factor and amplification rate were determined for the PFA operating in the quasi-static regime. To confirm the observed frequencies of resonance, an impedance analyzer is also utilized to measure the magnitude and phase of the PFA admittance.
Keywords: Homodyne optical interferometer; Nanometric displacement measurement; Piezoelectric flextensional actuator (PFA)